The Influence of Climate on Agricultural Decisions for Three European Crops: A Systematic Review - Mihailescu, Elena; Bruno Soares, Marta (Frontiers in Sustainable Food Systems, 2020)
The severity and uneven distribution of the expected climate change impacts across climate-sensitive agricultural areas, and the cropping systems operated within, call for identification and effective management of these impacts. The climate services have the potential to help identifying and adequately addressing the expected changes in climate and their impacts on agricultural production systems. However, the development of effective climate services is conditioned by the need to clearly understand the critical decisions that underpin end-users’ activities and how climate information can support those decision-making processes. This paper reviews and identifies the main decisions linked to key climate change impacts on the cropping systems of interest – olive, grape and durum wheat - in order to inform the development of climate services for these crops in the future. Our review results indicate two types of key findings: (i) the most common types of decisions across the three cropping systems address the increase in temperature, variability and uneven distribution of rainfall, occurrence of extreme events, and increased solar radiation; (ii) the most common decisions are likely to be affected by an increase in temperature above the maximum supported by the three crops, or in combination with other impacting climate changes. These decisions mainly relate to irrigation and other water stress reducing measures (olive, durum wheat), choice of varieties (grape, durum wheat), clones and rootstocks (grape), training system and vine load (olive, grape), canopy management (olive, grape), change in planting/sowing and harvest date (olive, durum wheat), pest and disease management (grape), allocation/choice of cultivation area (grape, durum wheat), use of decision support tools (grape), and crop insurance (durum wheat). In these decision-making contexts, the timely availability of climate information on temperature increase and rainfall variability can be used for developing climate services to effectively support the affected decisions. Although this paper does not provide an exhaustive analysis, the entry points identified can be considered as starting points for informing the development of climate services to further support the adjustment of decision making for the identified olive, grape, and durum wheat cropping systems, as well as similar decision-making contexts beyond those identified here.